Consumer technology brands and the source of their performance - Jorge Vera (Cogent Business & Management, 2021)
Over the past 20 years, consumer technology products have significantly impacted consumers' purchasing patterns and behaviors. The companies catering to this market have demonstrated unprecedented innovation and financial performance. Therefore, it is important to understand how consumers process such brands in forming their product preferences. Consumer technology brands comprise certain products-smartphones, tablets, smartwatches, music devices, and laptops-that fulfill a complex mix of numerous functional and emotional needs, such as joy, socialization, group acceptance, and group recognition. This study proposes a conceptual framework to explain how brand loyalty for such products is built upon certain relevant brand perceptions. In an empirical post hoc study involving 320 technology product customers, measurements for the constructs involved were established, and a multi-category approach was adopted wherein respondents evaluated Apple, HP, Samsung, and Sony products. A statistical structural model is presented wherein the relationships proposed in the hypotheses are tested and supported. It is established that brand perceptions of innovativeness, benefits, and identification are likely to be strong antecedents of brand loyalty. Unlike previous literature, this study measures perceived benefits at the parent-brand level rather than at that of the product-category.
Keywords: 650; brand innovativeness; perceived benefits; identification with the brand; affective loyalty; purchase intentions; behavioral loyalty; technology brands